Sulfonamides determination in chicken meat products from Malaysia - Cheong, C. K.; Parvaneh, Hajeb; Selamat, Jinap; Mohammad Rashedi, Ismail Fitry (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2010)
Sulfonamides (SAs), synthetic antibiotics, are commonly used by veterinarians in chicken for therapeutic, prophylactic or as growth promoter and halt the growth of bacteria in animal production. Four common SAs, Sulfadiazine (SDZ), Sulfamethazine (SMZ), Sulfamethoxazole (SMX) and Sulfaquinoxaline (SQX), were determined in chicken breast and liver samples using reverse phase HPLC using UV detector at 266nm. The concentration of SAs detected in samples from 11 states in Peninsular Malaysia ranged from 0.006-0.062 µg/g in breast meat samples and 0.08-0.193 µg/g in liver samples. Except for sample from Johor, concentration of SAs in all the samples were lower than MRLs established by Malaysia (0.1 µg/g). Exposure of sulfonamides in Malaysian consumers ranged from 0.002-0.088 µg/kg body wt. /day. The highest value of sulfonamides exposure was found in Johor with an estimated daily intake (EDA) of Sulfamethoxazole (SMX) in Johor.